Engagement and outcomes of cancer patients referred to a tobacco cessation program at a National Cancer Institute‐designated cancer center. (29th November 2022) - Westergaard, Sarah A.; Rupji, Manali; Franklin, Lauren E.; Behera, Madhusmita; Ramalingam, Suresh S.; Higgins, Kristin A.
Abstract: Introduction: Tobacco cessation is a critical but challenging intervention for cancer patients. Our National Cancer Institute‐designated Comprehensive Cancer Center instituted a tobacco cessation program in 2019. This manuscript reports on the first 2 years of our experience. Methods: Patients were referred to the program by their care team, and a certified tobacco treatment specialist contacted patients remotely and provided behavioral therapy and coordinated pharmacotherapy. We retrospectively captured data from patients with a cancer diagnosis referred to the tobacco cessation program. Univariate and multivariable logistic regression analyses with the backward elimination approach were performed to determine factors associated with patient acceptance of referral to the tobacco cessation program. Tobacco cessation rates after referral to the program were also captured. Results: Between July 2019 and August 2021, 194 patients were referred to the tobacco cessation program. Of the 194 patients referred, 93 agreed to enroll in the tobacco cessation program (47.9%), of which 84 requested pharmacotherapy (90.3%). Twenty‐four were able to cease tobacco use (25.8%). Only 7 patients out of the 101 patients (6.9%) who declined cessation services were successful ( p  < 0.001). On univariate logistic regression, race ( p  = 0.027) and marital status ( p  = 0.020) were associated with referral acceptance. On multivariable analysis, single patients (odds ratio [OR] = 0.33) and Caucasian patients (OR = 0.43) were less likely to accept a referral. Conclusions: Access to tobacco cessation services is a critical component of comprehensive cancer care. Our experience highlights the need to understand patient‐specific factors associated with engagement with a tobacco cessation program during cancer treatment. The use of pharmacotherapy is also a critical component of successful tobacco cessation. Abstract : At a National Cancer Institute‐designated cancer center, a tobacco cessation program was implemented, and under half of cancer patients engaged in the program. Single patients and Caucasian patients were less likely to engage with the program. Further efforts are needed to increase engagement of patients with tobacco cessation programs as we found higher tobacco cessation rates with program participation.